097 Surgical aortic valve replacement in high risk octogenerians vs transcatheter aortic valve implantation. (22nd September 2015) - Khavandi, A; Durack, A; Kesavan, S; Townsend, M; Hutter, J; Turner, M; Baumbach, A
Abstract : Introduction: Transcatheter aortic valve implantation (TAVI) is considered to subject less immediate procedural risk than surgical aortic valve replacement (AVR) in high risk elderly patients. Therefore high risk Octogenarians are now being considered for TAVI in preference to AVR. The evidence for this strategy and methods for patient selection are not established. The use of the Logistic Euroscore (LES) in this context has been questioned. We have prospectively compared our TAVI patient characteristics and outcomes with retrospective analysis of high risk Octogenarians who underwent AVR. Methods: The records of 273 patients aged 80 and over who underwent AVR at the Bristol Heart Institute between 1996 – 2008 were analysed. Patients with a Logistic Euroscore of 15 and above were identified as high risk including those that had concomitant bypass grafting. All TAVI procedures were performed with the Medtronic Corevalve system between Jan 2008 and Oct 2009. Data was collected prospectively as per the Central Cardiac Audit Database (CCAD) TAVI dataset and all patients were included for comparison. Results: Abstract 097 Table 1 80 AVR patients and 41 TAVI procedures were identified. The median LES was 20.7 (average age 83.5, male 51.2%) and 16.4 (average age 83.9, male 48%) respectively. More TAVI patients had previous cardiac surgery (19.5% vs. 15%). The postoperative stroke rate was 4.8% in the TAVI group vs. 6% for AVR. The rate of pacemaker implantation was greater in the TAVI group (24.4% vs. 11%). Mortality rates were significantly lower in the TAVI group (30 day mortality 2.4% vs. 14%, 90 day mortality 2.4% vs. 19%). There was a shorter median postoperative recovery for the TAVI patients prior to discharge (7 days vs. 11 days) and more patients were discharged directly home to indepedence (90.2% vs. 44%). Conclusion: In this historical, clinically selected group of Octogenarians the LES appears to correlate well with subsequent surgical risk of AVR. In our current cohort of high risk elderly patients undergoing TAVI there are comparatively lower mortality rates, shorter recovery times and earlier discharges home to independence. However, Corevalve patients are requiring more post-procedure permanent pacemakers. In elderly patients with symptomatic aortic stenosis it is appropriate to use LES as a factor to identify those who are likely to have a better outcome with TAVI compared to traditional AVR.